The Influence of Financial Distress and CSR on Firm Value Moderated by the Audit Committee - Winda Puspita Dewi; Robiur Rahmat Putra (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the influence of financial distress and Corporate Social Responsibility (CSR) on firm value, with the audit committee serving as a moderating variable. Methodology/approach: The data consisting of 105 observations were processed using the STATA software. Based on the model selection criteria, the random effects model was determined to be the most appropriate estimation approach. Results/findings: The results show that Financial Distress has a direct effect on Firm Value, whereas Corporate Social Responsibility does not have a direct impact on Firm Value. The Audit Committee is proven to significantly moderate the relationship between Financial Distress and Firm Value. Limitations: This study focuses only on financial distress, Corporate Social Responsibility (CSR), and audit committees. In fact, in the context of determining company value, there are many other factors that also have a significant influence. The results of this study leave a wide gap for further research development. Contributions: This study aims to emphasize the importance of the audit committee as a mechanism of corporate governance, particularly in mitigating the impact of financial distress on company value.  This research also provides recommendations for companies to strengthen the function and effectiveness of the audit committee in maintaining firm value. Conclusions: This study underscores the crucial role of the audit committee as a governance mechanism, specifically its effectiveness in mitigating the negative impact of financial distress on firm value. It recommends that companies enhance the functions and effectiveness of their audit committees to better maintain firm continuity and value.